MEAN PLATELET VOLUME AND DISTRIBUTION WIDTH IN TYPE II DIABETES - Luh Made Ayu Pradnyadari; Sri Ratna Dewi; I Made Sila Darmana (Meditory : The Journal of Medical Laboratory, 2025)
Background: Type 2 diabetes mellitus (T2DM) is a chronic metabolic illness characterized by persistent hyperglycemia, which raises the chance of macrovascular and microvascular complications. These issues are linked to increased platelet activation, aggregation, and thromboxane production.Objective: This study sought to assess the use of Mean Platelet Volume (MPV) and Platelet Distribution Width (PDW) as possible hematologic indicators for detecting vascular complications in people with T2DM. Methods: A retrospective cross-sectional research was conducted using the medical records of 141 T2DM patients treated at Sanjiwani Gianyar Hospital in 2023. Patients were split into two groups based on the presence or absence of vascular complications such as coronary artery disease, cerebrovascular disease, peripheral arterial disease, diabetic nephropathy, and diabetic retinopathy. MPV and PDW values were derived from routine Complete Blood Count (CBC) testing. The data were tested for normality, and any changes between groups were calculated using an independent samples t-test.Results: Patients with vascular complications had significantly higher MPV values (9.53 ± 1.30 fL) than those without complications (8.99 ± 0.96 fL), with a statistically significant p-value of 0. 018. However, the two groups' PDW values did not differ significantly (15.95 ± 0.44 vs. 15.91 ± 0.36; p = 0.582).Conclusions: MPV may be a useful and cost-effective hematological parameter associated with vascular complications in T2DM patients, but the clinical relevance of PDW is unclear and requires more research.